2020
DOI: 10.5406/amerjpsyc.133.3.0295
|View full text |Cite
|
Sign up to set email alerts
|

Attributing Social Meaning to Animated Shapes: A New Experimental Study of Apparent Behavior

Abstract: In 1944, Heider and Simmel reported that observers could perceive simple animated geometric shapes as characters with emotions, intentions, and other social attributes. This work has been cited over 3,000 times and has had wide and ongoing influence on the study of social cognition and social intelligence. However, many researchers in this area have continued to use the original Heider and Simmel black-and-white video. We asked whether the original findings could be reproduced 75 years later by creating 32 new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…This format can easily be implemented as a non-proctored, online assessment that makes it convenient for organizational research. The animations used in the Shapes Test have been found to evoke a similar degree of social attribution compared to the original Heider and Simmel film (Ratajska et al, 2020). Scores on this test also correlate positively with other validated social intelligence measures, including the Reading the Mind in the Eyes test (Baron-Cohen et al, 2001) and the Situational Test of Emotion Understanding (MacCann & Roberts, 2008), while displaying discriminant validity from measures of verbal ability or abstract reasoning (Brown et al, 2019).…”
Section: Origins Of Animated Shape Tasksmentioning
confidence: 92%
See 1 more Smart Citation
“…This format can easily be implemented as a non-proctored, online assessment that makes it convenient for organizational research. The animations used in the Shapes Test have been found to evoke a similar degree of social attribution compared to the original Heider and Simmel film (Ratajska et al, 2020). Scores on this test also correlate positively with other validated social intelligence measures, including the Reading the Mind in the Eyes test (Baron-Cohen et al, 2001) and the Situational Test of Emotion Understanding (MacCann & Roberts, 2008), while displaying discriminant validity from measures of verbal ability or abstract reasoning (Brown et al, 2019).…”
Section: Origins Of Animated Shape Tasksmentioning
confidence: 92%
“…A frame from the original Heider and Simmel (1944) film is displayed on the left (a) and a frame from one of the Social Shapes Test animations is shown on the right (b). This figure also appears in Ratajska et al (2020) descriptions provided by test takers after viewing the shape animations (Klin, 2000). This is an obstacle to organizational use where assessments are typically administered and scored electronically without a proctor or administrator (Tippins, 2009).…”
Section: Origins Of Animated Shape Tasksmentioning
confidence: 99%
“…It is not something we necessarily notice or reflect on, but our knowledge of the physical world makes social events meaningful. Heider & Simmel (1944;Ratajska et al, 2020) demonstrated this in their classic study of social perception: shapes moving on a screen become meaningful social agents with interpretable goals, beliefs, desires, emotions, and relationships under certain physical conditions. Most reviews of this work focus on the autonomous movement of the shapes, as autonomous movement is a salient cue to agency, and potentially a core-cognition of agents from birth (Leslie, 1995;Spelke & Kinzler, 2007;Xu, 2016).…”
Section: Crossing Domains: the Physics Of Social Imaginationmentioning
confidence: 95%
“…In their classic study, Heider & Simmel (1944;Ratajska et al, 2020) demonstrated how physical understanding informs social perception: shapes moving on a screen become meaningful social agents with interpretable goals, beliefs, desires, emotions, and relationships under certain physical conditions.…”
Section: Crossing Domains: the Physics Of Social Imaginationmentioning
confidence: 99%
“…In their classic study, Heider and Simmel (1944); Ratajska et al, 2020) demonstrated how physical understanding informs social perception: shapes moving on a screen become meaningful social agents with interpretable goals, beliefs, desires, emotions, and relationships under certain physical conditions. Most reviews of this work focus on the autonomous movement of the shapes, as autonomous movement is a salient cue to agency, and potentially a core‐cognition of agents from birth (Leslie, 1995; Spelke & Kinzler, 2007; Xu, 2016).…”
Section: Crossing Domains: the Physics Of Social Imaginationmentioning
confidence: 99%